Proposed Encryption and Key Generation Method Based on Geffe Generator, Genetic Algorithm, and DNA Coding - Soukaena Hassan Hashem (Journal of Madenat Alelem University College, 2018)
After the evolution in the digital world, it has become difficult to the preservation of information in the channels of communication; for this reason using of encryption methods is employed to provide security and to ensure access of information properly to the authorized persons and to ensure that the information is not manipulated and changed by others. Encryption methods are divided into two types one type is depended on using two keys (Public and Private key) while the other type is depended on using one secret key founded in both sides (Sender and Receiver). The encryption methods which depend on using two keys (Public and Private keys) sometimes are not secure because the predication of secret key is possible by using special calculations on the public key, the unauthorized person do this calculation .For this reason the methods which depend on private key are used where only authorized persons to send and receive the information have the private key. In this paper a proposed encryption method is presented based on using the Geffe Generator, Genetic algorithm, S-box and DNA coding. Since these will be used to generate special key. In the proposed method present three types of keys will be used in the encryption which are (Specified, Generated, and Static) which make it difficult to know the real key and the real secret text characters